Lateralization of Brain Activation in Fluent and Non-Fluent Preschool Children: A Magnetoencephalographic Study of Picture-Naming - Sowman, Paul F.; Crain, Stephen; Harrison, Elisabeth; Johnson, Blake W. (Frontiers in Human Neuroscience, 2014)
The neural causes of stuttering remain unknown. One explanation comes from neuroimaging studies that have reported abnormal lateralization of activation in the brains of people who stutter. However, these findings are generally based on data from adults with a long history of stuttering, raising the possibility that the observed lateralization anomalies are compensatory rather than causal. The current study investigated lateralization of brain activity in language-related regions of interest in young children soon after the onset of stuttering. We tested 24 preschool-aged children, half of whom had a positive diagnosis of stuttering. All children participated in a picture-naming experiment whilst their brain activity was recorded by magnetoencephalography (MEG). Source analysis performed during an epoch prior to speech onset was used to assess lateralized activation in 3 regions of interest. Activation was significantly lateralized to the left hemisphere in both groups and not different between groups. This study shows for the first time that significant speech preparatory brain activation can be identified in young children during picture-naming and supports the contention that, in stutterers, aberrant lateralization of brain function may be the result of neuroplastic adaptation that occurs as the condition becomes chronic.